CYP2J2∗7 Genotype Predicts Risk of Chemotherapy-Induced Hematologic Toxicity and Reduced Relative Dose Intensity in Ethiopian Breast Cancer Patients - Ahmed, Jemal Hussien; Makonnen, Eyasu; Yimer, Getnet; Seifu, Daniel; Bekele, Abebe; Assefa, Mathewos; Aseffa, Abraham; Howe, Rawleigh; Fotoohi, Alan; Hassan, Moustapha; Aklillu, Eleni (Frontiers in Pharmacology, 2019)
Chemotherapy induced hematologic toxicity is the primary reasons of dose reductions and/or delays, low relative dose intensity (RDI), and predicts anticancer response. We investigated the incidence and predictors of chemotherapy-induced hematologic toxicities and reduced RDI in Ethiopian breast cancer patients, and the implication of genetic variations. Breast cancer patients (n=249) were enrolled prospectively to receive cyclophosphamide based chemotherapy. Hematological toxicity were monitored throughout chemotherapy cycle. The primary and secondary outcomes were incidence of grade 3 or 4 hematologic toxicity and reduced RDI, respectively. CYP2B6*6, CYP3A5*3, CYP2C9 (*2,*3), CYP2C19 (*2,*3), CYP2J2*7, and POR*28 genotyping were done. Cox proportional hazard and logistic regression were used to estimate risk predictors of toxicity and reduced RDI, respectively. Majority (73.5%) of the patients were < 45 years of age. The incidence of grade 3 or 4 hematological toxicity was 51.0% (95% CI = 44.54 – 57.46%). Multivariate Cox proportional hazard and logistic regression indicated CYP2J2*7 genotype (Hazard ratio (HR) = 1.819; 95% CI, 1.141 – 2.899), pretreatment grade 1 leukopenia (HR = 2.748; 95% CI, 1.466 - 5.149) or grade 1 or 2 neutropenia (HR = 2.746; 95% CI, 1.732 – 4.353), as significant predictors of chemotherapy induced hematologic toxicities. 56.6% (95% CI = 50.3% - 62.9%) of the patients received reduced RDI. Higher risk of reduced RDI was associated with CYP2J2*7 allele carriers (AOR = 2.793; 95% CI, 1.208 - 6.456), BMI ≤ 18.4 kg/m2 (Adjusted odds ratio (AOR) = 5.975; 95% CI, 1.361 – 26.227), baseline grade 1 leukopenia (AOR = 6.092; 95% CI, 1.238 – 29.98), and baseline neutropenia (grade 1 or 2) (AOR = 3.37; 95% CI, 1.412 – 8.045). The odds of receiving reduced RDI was lower in patients with CYP2B6 *6/*6 genotype (AOR = 0.198; 95% CI, 0.055 – 0.771). We report high rates of chemotherapy-induced hematological toxicities causing larger proportion of patients to receive reduced RDI in Ethiopian breast cancer patients. Patients carrying CYP2J2 *7 allele and with low baseline WBC or ANC are at a higher risk for chemotherapy induced hematologic toxicities and receiving reduced RDI. Such patients require prior support and close follow up during chemotherapy.